2017
DOI: 10.5551/jat.37523
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia as a Predictive Marker for Progression of Nephrosclerosis: Clinical Assessment of Prognostic Factors in Biopsy-Proven Arterial/Arteriolar Nephrosclerosis

Abstract: Aim: The influence of serum urate on kidney disease is attracting attention, but the effects of uric acid (UA) on nephrosclerosis have not been elucidated.Methods: We reviewed data from 45 patients diagnosed with arterial/arteriolar nephrosclerosis. The renal outcomes of the arterial/arteriolar nephrosclerosis patients were assessed by performing logistic and Cox regression analyses. A Kaplan-Meier analysis was used to evaluate the impact of hyperuricemia (HU) on kidney survival. The renal outcomes of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Although renal AS might be associated with concurrent HT, it is sometimes found even in patients without HT. Previous studies showed that renal AS was associated with aging, postprandial hyperglycemia and hyperinsulinemia, low serum high‐density lipoprotein cholesterol, hyperuricemia, and chronic inflammation. In contrast, a BP <140/90 mmHg is recommended to reduce ESRD and cardiovascular disease among people with diabetes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although renal AS might be associated with concurrent HT, it is sometimes found even in patients without HT. Previous studies showed that renal AS was associated with aging, postprandial hyperglycemia and hyperinsulinemia, low serum high‐density lipoprotein cholesterol, hyperuricemia, and chronic inflammation. In contrast, a BP <140/90 mmHg is recommended to reduce ESRD and cardiovascular disease among people with diabetes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…89 This hypothesis was also supported by a subsequent study showing that hyperuricemia independently predicted renal survival in patients with biopsy-proven arteriolosclerosis. 90 Moreover, hyperuricemia was found to increase the risk of segmental glomerulosclerosis, tubular atrophy, and interstitial fibrosis after adjustment for serum creatinine, age, and blood pressure. 91 Whether hyperuricemia may also accelerate the progression of specific renal diseases is still uncertain.…”
Section: Hyperuricemia and Chronic Kidney Diseasementioning
confidence: 96%
“…The precise mechanism of the nephrotoxicity of HU also remains unknown. However, HU has been found to induce systemic hypertension and afferent arteriolar sclerosis in animal models [47] [48], and high serum UA levels have been reported to be associated with renal arteriolosclerosis in humans [4] [49] [50].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the serum uric acid (UA) on renal prognosis of CKD patients has recently been attracting attention [3], and our group has reported finding that the serum UA value can serve as a predictor of progression of kidney disease in biopsy-proven nephrosclerosis patients [4]. However, because the serum UA elevation due to the decreased renal UA clearance in CKD patients makes it difficult to assess the role of UA in the progression of CKD, the predictive value of UA in regard to the progression of CKD remains a matter of controversy [5]- [11].…”
Section: Introductionmentioning
confidence: 99%